(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
When a currency note of a particular denomination ceases to be a legal tender, it is termed as demonetisation. The Indian government had demonetised bank notes on two prior occasions—once in 1946 and then in 1978—and in both cases, the goal was to combat tax evasion by black money held outside the formal economic system. Similarly, on 8 November 2016, the Government of India announced the demonetisation of all ₹500 (US7.80) and ₹1,000 (US16) banknotes of the Mahatma Gandhi Series. The government claimed that the action would curtail the shadow economy and crack down on the use of illicit and counterfeit cash to fund illegal activity and terrorism. On the other hand, Government wanted the less cash economy because cash is the key of corruption and black money. Demonetisation is going to be a landmark in the history of the Indian economy.The long term effects of Demonetisation are yet to be ascertained. It is expected that it can improve the Indian economy in the long run by increasing tax compliance, financial inclusion, consequently improving the state of the economy. It can boost the GDP by increasing the availability of funds for lending and also by reducing transaction costs if the economy moves to digital modes of payments.In the paper, we try to find out the impact of demonetisation on GDP, daily wage workers, on small scale industry, on black money, on inflation, on terror funding, toward digital economy etc.